2020
DOI: 10.1111/lcrp.12166
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitness metamemory predicts identification performance in biased and unbiased line‐ups

Abstract: Purpose. Distinguishing accurate from inaccurate identifications is a challenging issue in the criminal justice system, especially for biased police line-ups. That is because biased line-ups undermine the diagnostic value of accuracy post-dictors such as confidence and decision time. Here, we aimed to test general and eyewitness-specific self-ratings of memory capacity as potential estimators of identification performance that are unaffected by line-up bias.Methods. Participants (N = 744) completed a metamemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…47,48 ] to obtain an estimate of the innocent-suspect identifications in culprit-absent lineups. However, it is well known that real-world lineups are often not perfectly fair and there is strong evidence of a biased selection of suspects in unfair lineups [e.g., [56][57][58] ]. If the 2-HT eyewitness identification model is valid, then the biased selection of suspects in unfair lineups should be sensitively reflected in parameter b.…”
Section: Manipulations Of Biased Suspect Selection: Validation Of Par...mentioning
confidence: 99%
“…47,48 ] to obtain an estimate of the innocent-suspect identifications in culprit-absent lineups. However, it is well known that real-world lineups are often not perfectly fair and there is strong evidence of a biased selection of suspects in unfair lineups [e.g., [56][57][58] ]. If the 2-HT eyewitness identification model is valid, then the biased selection of suspects in unfair lineups should be sensitively reflected in parameter b.…”
Section: Manipulations Of Biased Suspect Selection: Validation Of Par...mentioning
confidence: 99%
“…Both are consistently found to predict eyewitness accuracy, though there is room for improvement. Research has identified a few other potential reflector variables, but more research is needed on these: memory for fillers (Charman & Cahill, 2012), metamemory (Saraiva et al, 2020a;2020b), response bias (Baldassari, Kantner, & Lindsay, 2019), and face identification ability (Bindemann et al, 2012). We were particularly interested in the role of decision processes.…”
Section: Eyewitness Decision Processes: a Valid Reflector Variablementioning
confidence: 99%
“…For example, where an innocent suspect stands out in a lineup, eyewitnesses tend to be overconfident and as a result, high-confidence identifications become less accurate and leaving the usage of high-confidence ratings as an indicator of probative value within courts premature (Berkowitz, Garrett, Fenn, & Loftus, 2022). Saraiva, van Boeijen, Hope, Horselenberg, Sauerland, & van Koppen (2020) suggest that eyewitnesses may use a potentially misleading heuristic-perceived task difficulty-as a proxy for underlying discriminability, especially where fillers become implausible options or where memory self-efficacy is rated as very high or very low. Thus, it seems that, as true Bayesian observers, eyewitnesses apply all available information during their eyewitness identification decisions, including metacognitive information not currently included in existing SDT models of eyewitness memory.…”
Section: Exploring the Mapping Of Certainty To Identification Decisionsmentioning
confidence: 99%